PEMBENTUKAN PERATURAN DAERAH MELALUI PENDEKATAN NILAI SIRI NA PACCE SEBAGAI UPAYA PENCEGAHAN SIKAP KORUPSI (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to analyze and find out two things, namely how should the regulation of anti-corruption education through planting the cultural values ​​of Siri 'Na Pacce in Kab. Bone and to provide consideration and input for the district government. Bone in formulating policies related to anti-corruption education through the inculcation of the cultural values ​​of Siri 'Na Pacce. This research uses empirical normative research method. The results of this study indicate that the higher the cultivation of the siri na pacce cultural value of a person, the smaller the corrupt behavior that grows in him and corrupt practices or known in Bugis language Manre Pasoso can be avoided. This is because the existing officials and law enforcers can suppress corrupt behavior by trying to prioritize the value of siri in the traditional government processes of the Bugis community so that the influence and opportunity to commit criminal acts of corruption can be reduced. In order for this to run as desired, the authors suggest that the district government of Bone form a regulation on anti-corruption education through the method of cultivating the cultural values ​​of Siri 'Na Pacce in the District. Bone.